Expressão, purificação e caracterização das luciferases de Cratomorphus distinctus (Lampyridae) e Euryopa clarindae (Phengodidae) e sondagem de suas aplicabilidades - Benites, Gabrielle Rodrigues (Universidade Federal de São Carlos, 2024)
Luciferases are the enzymes that catalyze the bioluminescence reaction in organisms such as beetles. Bioluminescence has been used for bioanalytical purposes for decades, including ATP detection assays, enzymatic assays, microbiological contamination of products in the food industry, as a reporter gene for pollutant biosensors, intracellular pH and heavy metal indicators, and bioimaging. Our research group has cloned the largest number and variety of beetle luciferases in the world, some already having bioanalytical applications, however there are still several luciferases and mutant forms with interesting properties that we have produced, but which have not yet been well characterized and applied. With the aim of expanding the range of applications, especially in biosensors for pH and potentially toxic metals, we carried out the characterization of the pH-sensitive luciferases from the lampyrid C. distinctus and the orange light-emitting luciferase from the phengodid E. clarindae. To achieve this, we subcloned the luciferase cDNA from C. distinctus and E. clarindae into a pCold vector, transformed E. coli BL21DE3 bacteria and expressed and purified the two luciferases by affinity chromatography on nickel-agarose resin. The tests showed that the C. distinctus luciferase has a high catalytic efficiency for ATP and lower for LH2, when compared to other lampyrid luciferases, in addition to having excellent sensitivity to pH and metals, especially mercury. The E. clarindae luciferase showed a high KM for LH2 and low for ATP, when compared to luciferases from other phengodids. Thus, C. distinctus luciferase has potential applicability as a mercury and pH sensor protein; while the insensitive luciferase from E. clarindae has potential as a reporter gene. Furthermore, the orange light-emitting luciferase from E. clarindae constitutes another important model to understand the structure x bioluminescence spectra relationship in coleopteran luciferases and the origin of the different bioluminescence colors.
Expression, purification and characterization of luciferases from Cratomorphus distinctus (Lampyridae) and Euryopa clarindae (Phengodidae) and investigation of their applicability
Keywords: Luciferases; Biossensor; Biosensor; C. distinctus; E. clarindae; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA; CIENCIAS BIOLOGICAS::GENETICA